Applying Autocad 2004 (photocopy) - T.Wohlers Terry (McGraw-Hill, 2004)
Applying AutoCAD 2004 is a comprehensive, basic CAD textbook providing step-by-step instruction for new users of the AutoCAD computer-aided drafting and design software, version 2004. It covers the AutoCAD commands and functions used to create, edit, store, and print engineering drawings.